Determinants of income for Micro, Small and Medium Enterprises in Sleman Regency - Marfuah, Marfuah; Irfinanda, Salsabila Ofa; Rachmasari, Dian (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to determine the effect of own capital, people’s business credit, entrepreneurial attitude, business location, length of business and information technology on the income of Micro, Small and Medium Enterprises (MSMEs) in Sleman Regency. The population of this study is MSME players in 17 Kapanewon in Sleman Regency in 2021 as many as 90,118 business units. Using the convinenience sampling technique, 110 respondents were selected as research samples. Based on multiple linear regression analysis, it is concluded that own capital, people’s business credit, entrepreneurial attitude, length of business, and information technology have proven to have a significant positive effect on the income of MSMEs in Sleman Regency. Meanwhile, the location of the business does not have a significant positive effect on the income of MSMEs in Sleman Regency. The results of this study have implications for MSME actors to be able to increase their income, it is hoped that they can increase the number and ability to manage business capital both from their own capital and from borrowed capital, especially people’s business credit. In addition, MSME actors are also expected to always improve entrepreneurial attitudes, experience and skills in running a business and increase their understanding and ability to use information technology to support the operation and sale of products or services produced.